Organisational Prerequisites to Fund, Implement and Sustain Māori Health Promotion in a Primary Care Setting - Brown, Rachel (Auckland University of Technology, 2010)
Māori are the indigenous people of New Zealand. As a population group Māori have on average the poorest health status of any ethnic group in New Zealand (Ministry of Health, 2007). Much of this disproportionate ill-health is linked to manageable and/or preventable conditions. Given this, there is much scope for effective Māori health promotion in particular, as the Māori population is relatively young. The primary objective of the case study research was to determine the organisational pre-requisites necessary to fund, implement and sustain Māori health promotion within a primary care setting. Secondary aims were to; identify how health promotion is perceived within a ‘Māori’ primary health care setting, identify existing health promotion practice, and test the feasibility of implementing a current Māori health promotion framework. The case study research was informed by 19 key informant interviews and two focus group sessions. A literature review including an organisational document review was also undertaken. Findings indicated that many of the pre-requisites necessary for effective Māori health promotion implementation sat outside the scope of the organisation and needed to come from a variety of sources including the Ministry of Health, District Health Board’s (DHB’s), community organisations and health providers, whānau (family), hapū (sub tribe) and iwi (tribe), including support from other sectors. The research also found a number of underlying issues that impacted greatly on the health of the Māori population within the PHO. These issues need to be addressed at a number of levels and given high New Zealand priority. In testing the feasibility of a current Māori health promotion model (Kia Uruuru Mai a Hauora) it was considered by participants to fit well with the goals, principles and values of the case study site and within primary health care in general, complementing critical health care service delivery components that already exist. The study’s conclusion found that there was much scope for Māori health promotion that was fully supported, recognised, and adequately and appropriately resourced by the New Zealand Government, Ministry of Health and DHB’s in order to provide long term cost effective and sustainable health benefits.
Keywords: Maori health promotion; primary care; health promotion; health promotion models; Maori health